(untitled) - Madlenakova, Lucia (Doprava a spoje, 2006)
The postal industry and market are about to change very decisively and more rapidly than over before. The postal sector, customers are becoming increasingly assertive in exercising their rights and wishes. The Slovak postal market is connecting to the European postal market. It is necessary to put attention on the new advantages and threats, which are connect with opening and liberalization of the market and ensuring the universal postal service, its conditions, problem and perspective of national operator.